Manufacturing polymeric porous capsules. Issue 28 (17th March 2022) - Contini, Claudia; Hu, Wenyi; Elani, Yuval
Abstract : The review paper outlines the current state-of-the-art strategies adopted to fabricate polymeric porous capsules which represent a novel supramolecular construct that broadens the applicability and versatility of self-assembled polymeric systems. Abstract : Polymeric porous capsules represent hugely promising systems that allow a size-selective through-shell material exchange with their surroundings. They have vast potential in applications ranging from drug delivery and chemical microreactors to artificial cell science and synthetic biology. Due to their porous core–shell structure, polymeric porous capsules possess an enhanced permeability that enables the exchange of small molecules while retaining larger compounds and macromolecules. The cross-capsule transfer of material is regulated by their pore size cut-off, which depends on the molecular composition and adopted fabrication method. This review outlines the main strategies for manufacturing polymeric porous capsules and provides some practical guidance for designing polymeric capsules with controlled pore size.